Angels on our shoulders - Heiberger, Edward Francis ([Place of publication not identified] : [publisher not identified], 2012)
The author describes growing up in Dubuque, Iowa, and serving in the Air Force during World War II.
Boyhood days -- Stateside service -- Overseas combat missions.
Cover title.
Keywords: Heiberger, Edward Francis; United States. -- Army Air Forces -- Aerial gunners -- Biography; World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Aerial operations, American; Dubuque (Iowa) -- Biography; Biographies